An exploratory study of health literacy in the context of health information technology utilization - Ducut, Mary Jastine B.; Santos, Mark Anthony A. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2020)
There has been an observed interest in the phenomenon of self-qualification through the use of health information technology (HIT) in recent years which has been claimed to positively affect personal performance, nutrition, and understanding of one’s mind and body. This is evident in the growth of tracking devices and applications offered in the market. Statistics on mobile phone users, internet users, and online activity in the Philippines seem to suggest the potential for presentation of this trend in the country. However, multiple studies show that the utilization of the technology is complex, requiring new ways of being literate. This study mainly aimed to understand whether health literacy influences the use of HIT tools. It also aimed to uncover the perceptions of Filipino adults on HIT. The relationships among HIT tools used, perceived health literacy and actual health literacy were also examined. Lastly, the study aimed to investigate the influence of health literacy on their perceptions of the technology.

The study utilized volunteer response sampling to gather respondents, with calls to participation sent mainly through social media platforms. The online survey disseminated was composed of two health literacy assessment tools, NVS and eHEALS, and close – ended questions concerning demographics and perception of HIT.

Results from a survey of 105 respondents show that mHealth applications were used more than smartwatches and tracking devices and that perceived and actual health literacy levels were adequate. However, the respondents’ perception of their health literacy level were significantly higher than their actual health literacy level. Perceptions of HIT were generally positive except on the issues of data sharing Results also show that perceived health literacy were better predictors of adoption than actual health literacy.

In this study, perceived health literacy and actual health literacy were examined to understand whether they influence the utilization of HIT. The study’s findings indicate that health literacy, specifically perceived health literacy, influences HIT adoption and use. Aligning with this, recommendations were given to aid the effective utilization and adoption of the technology.
Thesis
Keywords: Health literacy; Medical innovations